THE RELATION BETWEEN PROTEIN AND FERRUM CONSUMPTION WITH HAEMOGLOBIN CONCENTRATION OF YOGYAKARTA STATE UNIVERSITY (UNY) STUDENTS - Yuliati Yuliati; Tutik Rahayu; Kartika Ratna Pertiwi (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2015)
This study aims to investigate the protein and ferrum consumption with the requirement nutrition and to study their relation with haemoglobin (Hb) concentration of UNY students, through cross sectional model with applying point time approach. The samples are UNY students taken from incidental technic. The food consumption pattern measured by food frequency instrument while the consumption level was measured by recall diet method. Hb concentration was determined using sahli method. The height and body weight were also collected to complete the data. The descriptive analysis and product moment correlation of the data resulted 95% significancy level. The 91,4% respondents showed the low protein consumption and all samples (100%) indicated low ferrum consumption. The correlation between protein and ferrum with Hb concentration provided a 95% significancy level. Keywords: protein, ferrum, haemoglobin